PROPOSED PROJECT IMPLEMENTATION PERFORMANCE MEASUREMENT IMPROVEMENT IN PT. LEN INDUSTRI (PERSERO) - Kurnia, Ridwan
PT. Len Industri (Persero) had a tremendous financial performance in 2018. They booked profit before tax realization of Rp211,351.87 million or 133.23% of target, NPM (Net Profit Margin) achieved 2.5% or IDR133 billion level. However, the profit margin realization was far from expected, especially for non-state budget (APBN) based projects. At the end of 2018, PT LEN has lost (-263 billion) caused by the implementation of the project closing; furthermore, it caused some interest and debt. PT. Len implemented a project management perspective to support the project, which has been acknowledged as the backbone of the company business. High expectations regarding the project management performance from the different stakeholders often create a silo execution. From the upstream, sales achievement didn’t directly can be converted into a net profit; thus, the company was trapped in the working capital deficiency. In the downstream, the project planning was not appropriately prepared, thus creating some problems in the execution, and project tends to be a firefighting. It was hard to achieve the KPI goals; project efficiency improvement, on-time project delivery, and creating a value and more profit margin for the company, although the company have implemented performance measurement using The Balanced Scorecard. From the analysis, the author found an un-ideal BSC implementation at the company. The current BSC didn’t align with the project performance directly. The project implementation also experienced some difficulties as the company was unable to monitor its performance. And too many generic attributes which was not related and impacted to the performance. This research will conduct an analysis to determine the main issue that affected PT. Len’s performance; and propose a solution for PT. Len’s improvement in the project management performance measurement. The research will take part in TIKNAV business unit from all value chains and conduct a focus group discussion with several employees, which are representing some managerial level, executives and related to the project implementation. The results showed that the performance measurement with the modified BSC would have a better impact on the performance. It reflected from the higher correlation value to the ideal project performance. The previous BSC has a 0.035. coefficient of determination is 14.89%. This value indicates that 14.89% of the changes in the Performance Measurement System are caused by the implementation of The Balanced Scorecard. Meanwhile, the modified BSC has a higher Pearson correlation value of 0.593, and the coefficient of determination is 35.17%, indicating that the changes in the Performance Measurement System are caused by the implementation of the Modified The Balanced Scorecard. The project management itself will be adopted from PMBOK 6, which the company has implemented into PMOG-01. This research will help PT. Len in monitoring and measuring their project performance, moreover having a comprehensive Balanced Scorecard as the company’s performance measurement. Furthermore, it will help the business decision related to the project performance.